2009
DOI: 10.4018/irmj.2009070102
|View full text |Cite
|
Sign up to set email alerts
|

Software Development Methodologies in Organizations

Abstract: The theories of social exchange, task-technology fit, and technology acceptance are utilized in a field study of software development methodologies. This investigation includes the effects of user experiences on perceptions of acceptance and usage of a methodology. More specifically, perceptions of the outputs and deliverables from a methodology and perceptions of challenges and obstacles to using and applying a methodology were found to significantly and positively influence perceived usefulness and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…In support of this practice, scholars like Laporte, Seguin and Boas (2013) posited that "the ability of organizations to compete, adapt, and survive depends increasingly on software" (p.32). However, in most cases these expected benefits have not been realized because the software development community has been plagued with the delivery of poor quality software and failed information systems projects (Agarwal & Tomar, 2014;Kacmar, McManus, Duggan, Hale & Hale, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this practice, scholars like Laporte, Seguin and Boas (2013) posited that "the ability of organizations to compete, adapt, and survive depends increasingly on software" (p.32). However, in most cases these expected benefits have not been realized because the software development community has been plagued with the delivery of poor quality software and failed information systems projects (Agarwal & Tomar, 2014;Kacmar, McManus, Duggan, Hale & Hale, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the categories that positively influence preference for agile methods are malleable and can thus inform management of software development teams adopting agile methods in regards to team formation, optimization, and retention. Our work adds to the continuing stream of research on adoption of development methodologies (Kacmar et al, 2009), developer attitudes and preferences (Hendersen et al, 2012) and complements research that explores issues such as methodology fit (Xu & Yao, 2014) and project commitment (Korzaan & Brooks, 2015) on organizational productivity.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies indicate that perceptions of methodology output, and perceptions about the obstacles encountered while applying a methodology, influence perceptions about usefulness and ease of use about the methodology (Kacmar, McManus, Duggan, Hale, & Hale, 2009). Changes in software development methodologies may also require changes in developer mindset (Armstrong, Nelson, Nelson, & Narayanan, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of these studies view software development methodologies as technology innovations and make use of technology adoption theories and models, such as Diffusion of Innovations Theory (DOI) and Technology Acceptance Model (TAM) (for e.g. [8,12,62,61]). Others apply sociological models such as the Theory of Planned Behaviour (TPB) and Triandis' Theory of Interpersonal Behavior (TTIB) to examine the development of the intention of individuals to use methodologies (for e.g.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
“…We suggest differentiating OU and PU based on other dimensions, influenced by purely personal interests (independent of organisational usefulness) such as materialism and enjoyment. Kacmar et al [61] conducted a field study of ISD methodologies, applying theories of social exchange, task-technology fit, and technology acceptance. They found that perceptions of the outputs and deliverables from a methodology, and perceptions of challenges and obstacles to using and applying a methodology, to significantly and positively influence perceived usefulness.…”
Section: Content Overviewmentioning
confidence: 99%